Bahasa Visual Kemasan Chitato - Lukitasari, Evelyne Henny (KOMUNITAS, 2014)
In the distribution of food to the customers in need of packaging that serves as s wrapper, tool safety of food in itand also serves as a messenger media products to consumers as well as a media campaign. Packaging as a medium of communication through visual language. A visual communication in conveying the message of a product it contains the signs that have meaning that can be understood by consumers. His article tries to explain and describe the meaning and significance of the visual is displayed on the packaging Chitato Potato Chips using semiotic analysis in oreder to understand the intent of the message to be delivered by Chitato Potato products to consumers.